2001
DOI: 10.1007/s004240100676
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation of the volume-sensitive cation channel TRP12 (OTRPC4) and volume-regulated anion currents in HEK-293 cells

Abstract: The detection of changes in volume and osmolality is an essential function in vertebrate cells. A novel member of the transient receptor potential (trp) family of ion channels, which is sensitive to changes in cell volume, has been described recently. Heterologous expression of TRP12 in HEK cells resulted in the appearance of a swelling-activated cation current. The permeability sequence of this cation current for various monovalent cations, as determined from shifts in reversal potential upon extracellular ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 26 publications
2
81
0
Order By: Relevance
“…1 A and 7A). This higher basal [Ca 2ϩ ] i can be attributed to the basal TRPV4 channel activity in the absence of stimuli (11,12,33). The finding that [Ca 2ϩ ] i in nonstimulated cells is not significantly affected by preincubation with the various PLA 2 blockers (Fig.…”
Section: Hypotonicity-induced Activation Of Trpv4 Is Not Mediated By mentioning
confidence: 80%
See 3 more Smart Citations
“…1 A and 7A). This higher basal [Ca 2ϩ ] i can be attributed to the basal TRPV4 channel activity in the absence of stimuli (11,12,33). The finding that [Ca 2ϩ ] i in nonstimulated cells is not significantly affected by preincubation with the various PLA 2 blockers (Fig.…”
Section: Hypotonicity-induced Activation Of Trpv4 Is Not Mediated By mentioning
confidence: 80%
“…They are distributed widely in mammalian tissues, but their specific physiological functions and activation mechanisms are often unclear. TRPV4, a member of the TRPV subfamily, was originally considered as a Ca 2ϩ -permeable sensor of cell volume (11)(12)(13)19), but later reports demonstrated that it can also be activated by phorbol esters (5), moderate heat (6,20), and AA metabolites (22). It is presently unknown how these completely different stimuli converge on a single molecular event: the opening of the TRPV4 conduction pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HEK293 cells were transiently transfected with the pCINeo/IRES-GFP/ rbECaC vector using previously described methods (15).…”
Section: Methodsmentioning
confidence: 99%